HUBUNGAN TINGKAT KECEMASAN PERPISAHAN DENGAN ORANG TUA TERHADAP MOTIVASI BELAJAR SANTRI DIPONDOK PESANTREN DARUSSALAM DESA NGESONG SENGON JOMBANG - Heri Triwibowo; Khoirunnisyak Khoirunnisyak (Bahasa Indonesia, 2017)
Student life / of student at traditional muslim school while studying at muslim boarding school is full of difficulty. Starting from academic difficulty, financial difficulty, sociocultural difficulty, surroudings difficulty etc, the difficulties will be more felt for students or students at traditionsl muslim school who are far from family or come from om threats to know the realitiship of searation unkiety level with parents to motivations to learn students on traditional muslim school Darussalam, ngesong sengon village, Jombang. The research design that is used is correlational analysis of population in this research is of all students on traditional muslim scool in class 1 junior high school and 1 high school in Sengon Village Jombang, Jombang Regency with sample resources 80 people, the technique using total sampling Independent variable in this research is anxiety and dependent variable Is the motivation, Data Analysis, Editing, coding, scoring Tabulating and cross tabulation. Based on the results of research can be concluded than half of respondents have moderate anxiety as many us 51people (63.8%). Half of respondent's motivation is moderate as many us 40 people (50%). The students on traditional muslim scool who have severe anxiety most 7 people (100%) have a weak motivation. This means that the more severe anxiety, the weaker the motivation to learn in students on traditional muslim scool There is anxiety relationship Farewell to Parents about Motivation Learning Students In Darussalam boarding school Ngesong Sengon Village Jombang. The new students on traditional muslim enter the boarding school should be active in following the activities at the boarding school, developing hobby and follow extracurricular in boarding school.